“EPIDEMIOLOGICAL STUDY OF VICTIMS OF TWO-WHEELER ROAD TRAFFIC ACCIDENTS” - Dr Aaqib Pervaiz Butt; Dr Mubashir Khaliq; Dr Basharat Hafiz; Dr Aaqib Suhail Mir (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Road traffic accidents (RTAs) involving two-wheelers pose a critical public health challenge in India, contributing significantly to morbidity and mortality. This prospective observational study analysed the epidemiological profile, injury patterns, and outcomes of 400 two-wheeler accident victims admitted to the Department of Surgery, Government Medical College, Jammu, over one year. The majority of victims were young males (mean age 24.33 years), with 88% being male and 87% being drivers. Helmet usage was low (24.5%), correlating with a high incidence of head and neck injuries (31.16%) and multiple trauma (74%). Behavioural risk factors included alcohol use (7.25%) and mobile phone use (3%). Most cases were managed conservatively (86.75%), with a mortality rate of 10.25%. The study underscores the urgent need for improved helmet compliance, stricter enforcement of traffic laws, public awareness campaigns, and enhancement of trauma care systems to reduce the burden of two-wheeler-related RTAs.